Psychological Contract Violation or Basic Need Frustration? Psychological Mechanisms Behind the Effects of Workplace Bullying - Sischka, Philipp E.; Melzer, André; Schmidt, Alexander F.; Steffgen, Georges (Frontiers in Psychology, 2021)
Workplace bullying is a phenomenon that can have serious detrimental effects on health, work-related attitudes, and the behavior of the target. Particularly, workplace bullying exposure has been linked to lower level of general well-being, job satisfaction, vigor and performance, and higher level of burnout, workplace deviance, and turnover intentions. However, the psychological mechanisms behind these relations are still not well understood. Drawing on psychological contract and self-determination theory, we hypothesized that perceptions of contract violation and the frustration of basic needs mediate the relationship between workplace bullying exposure and well-being, attitudinal, and behavioral outcomes. Self-reported data were collected among employees with different working backgrounds (N = 1,257) via Amazon’s Mechanical Turk in an online survey. Results showed that feelings of contract violation and frustration of basic needs accounted for unique variation in well-being, work satisfaction, burnout, vigor, and turnover intentions, pointing to individual contributions of both psychological mechanisms. However, when controlled for frustration of basic needs, feelings of psychological contract violation were no longer a mediator between workplace bullying exposure and work performance. Helping employees to deal effectively with workplace bullying exposure might buffer its negative effects and reduce their experienced frustration of basic needs, preserving their well-being, vigor, and work performance and, eventually, prevent burnout. The present study is the first to concurrently elucidate the proposed psychological mechanisms and unique contributions of psychological contract violation and frustration of basic needs in the context of workplace bullying.